Phytoremediation of Pb‐Contaminated Soil by Salicornia iranica: Key Physiological and Molecular Mechanisms Involved in Pb Detoxification. Issue 5 (23rd March 2017) - Kaviani, Elina; Niazi, Ali; Heydarian, Zohreh; Moghadam, Ali; Ghasemi‐Fasaei, Reza; Abdollahzadeh, Tayebe
Abstract : The heavy metal lead (Pb) is one of the most important environmental pollutants and abiotic stresses with harmful effects on all living beings including plants. In this study, Salicornia iranica was used in an attempt to phytoremediate Pb‐contaminated soil. Possible mechanisms of plant tolerance against Pb pollution and its detoxification were studied through expression analysis of Glutathione‐S‐transferase ( GST ) and measurement of involved key physiological components. Interestingly, promoter analysis of GST showed that there are some essential cis‐acting elements responsive to gibberellin, abscisic acid, salicylic acid, and myeloblastosis viral oncogene homolog (MYB) family binding sites involved in Pb detoxification. The concentration of chlorophyll a and b and carotenoids significantly decreased in plants grown on Pb‐contaminated soil for 90 days and in 90‐day‐old plants treated for 24 and 48 h (at a concentration of 1000 mg/kg Pb). The result of free proline measurement showed that it significantly increased in shoot tissue. The Pb absorption and its concentration increased in shoot tissue. In addition, the GST expression significantly increased as a result of the 100 mg/kg Pb treatment, but not at the higher concentration of 1000 mg/kg Pb. It was also observed that Pb accumulation did not influence plant growth parameters such as shoot and root lengths. Therefore, S. iranica is able to accumulate Pb in shoot tissue, and it may be useful in phytoremediation of Pb‐polluted soil. Abstract : In this study, the ability of Salicornia iranica for Pb absorption is evaluated. The results show that the Pb concentration increased in S. iranica tissues and Pb accumulation do not influence plant growth parameters. Finally, Salicornia can tolerate Pb accumulation with increasing of GST enzyme activity and proline accumulation. Therefore, S. iranica can be used in phytoremediation.